2018
DOI: 10.20944/preprints201807.0615.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Onchodermatitis: Where Are We Now?

Abstract: Onchocerciasis causes debilitating pruritus and rashes as well as visual impairment and blindness . Prior to control measures, eye disease was particularly prominent in savanna areas of sub-Saharan Africa whilst skin disease was more common across rainforest regions of tropical Africa. Mass drug distribution with ivermectin is changing the global scene of onchocerciasis. There has been successful progressive elimination in Central and Southern American countries and the World Health Organization has set a targ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 86 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…Major progress has been made concerning the control of onchocerciasis, initially by the OCP (1974–2002) and subsequently by the African Programme for Onchocerciasis Control (APOC, 1995–2015) and the Onchocerciasis Elimination Program for the Americas (OEPA, 1993–ongoing) [14]. New cases of blindness and severe skin disease are rare except in conflict zones, where instability has had a detrimental impact on programmes’ performance, and in areas of difficult access [15]. CDTI has indeed been very successful in many areas, and since 2010, the paradigm of onchocerciasis control has shifted to that of elimination [16].…”
Section: Current Onchocerciasis Elimination Programmesmentioning
confidence: 99%
“…Major progress has been made concerning the control of onchocerciasis, initially by the OCP (1974–2002) and subsequently by the African Programme for Onchocerciasis Control (APOC, 1995–2015) and the Onchocerciasis Elimination Program for the Americas (OEPA, 1993–ongoing) [14]. New cases of blindness and severe skin disease are rare except in conflict zones, where instability has had a detrimental impact on programmes’ performance, and in areas of difficult access [15]. CDTI has indeed been very successful in many areas, and since 2010, the paradigm of onchocerciasis control has shifted to that of elimination [16].…”
Section: Current Onchocerciasis Elimination Programmesmentioning
confidence: 99%
“…APOC reported that the DRC is a global reservoir of onchocerciasis [28] in which almost 38 million people are at risk [11], of whom approximately 13 million were affected in 2013; the number of people blinded was estimated at 70 thousand [17,28,29,30]. The most recently available data in the 2016 study Global Burden of Disease (GBD) estimated a global prevalence of 14.65 million [2] people, including 12.22 million suffering from the skin disease and 1.03 million cases of sight loss due to onchocerciasis [2]. Onchocerciasis is the third most common cause of blindness in the DRC after cataracts and glaucoma [11].…”
Section: Resultsmentioning
confidence: 99%
“…Onchocerciasis, also known as river blindness, volvulosis, or Robles disease, is a cutaneous filariasis [1], caused by the filarial nematode Onchocerca volvulus [2]. The worm infests the skin and eyes and is transmitted from an infected individual to a healthy individual via the bite of an infected black fly, belonging to the Simuliidae family [3].…”
Section: Introductionmentioning
confidence: 99%
“…32 These guidelines are expected to be revised by WHO in 2020, but it is clear that progress towards onchocerciasis elimination effort would benefit enormously by newer, more sensitive and specific diagnostic tests to verify that transmission of infection has been suppressed or interrupted. 71 volvulus in all elimination programs. 32 The serological threshold for stopping MDA is an Ov16 antibody prevalence of <0.1% among children aged 5-9 years (inclusive) who act as sentinels for recent infection.…”
Section: Diagnostic Tools In the Onchocerciasis Elimination Eramentioning
confidence: 99%